A study of 4D printing and functionally graded additive manufacturing. Issue 2 (3rd April 2017) - Pei, Eujin; Loh, Giselle Hsiang; Harrison, David; Almeida, Henrique de Amorim; Monzón Verona, Mario Domingo; Paz, Rubén
Abstract : Purpose: The purpose of this paper is to extend existing knowledge of 4D printing, in line with Khoo et al. (2015) who defined the production of 4D printing using a single material, and 4D printing of multiple materials. It is proposed that 4D printing can be achieved through the use of functionally graded materials (FGMs) that involve gradational mixing of materials and are produced using an additive manufacturing (AM) technique to achieve a single component. Design/methodology/approach: The latest state-of-the-art literature was extensively reviewed, covering aspects of materials, processes, computer-aided design (CAD), applications and made recommendations for future work. Findings: This paper clarifies that functionally graded additive manufacturing (FGAM) is defined as a single AM process that includes the gradational mixing of materials to fabricate freeform geometries with variable properties within one component. The paper also covers aspects of materials, processes, CAD, applications and makes recommendations for future work. Research limitations/implications: This paper examines the relationship between FGAM and 4D printing and defines FGAM as a single AM process involving gradational mixing of materials to fabricate freeform geometries with variable properties within one component. FGAM requires better computational tools for modelling, simulation and fabrication because current CAD systems are incapable of supporting the FGAM workflow. Practical implications: It is also identified that other factors, such as strength, type of materials, etc., must be taken into account when selecting an appropriate process for FGAM. More research needs to be conducted on improving the performance of FGAM processes through extensive characterisation of FGMs to generate a comprehensive database and to develop a predictive model for proper process control. It is expected that future work will focus on both material characterisation as well as seamless FGAM control processes. Originality/value: This paper examines the relationship between FGAM and 4D printing and defines FGAM as a single AM process that includes gradational mixing of materials to fabricate freeform geometries with variable properties within one component.